Applying Opinion Mining in e-Leaming - Le, Thao N.T. (Journal of Technical Education Science, 2009)
Recently, we have witnessed an explosive growth of e-learning. More and more learning contents have been published and shared over the Internet. "Putting the Learner at the Center " is the next-generation innovation emphasizes enabling learning in e-learning environments. Therefore, how to know learner’s opinion on the course-wares, the teachers, the charge or something else of the e-learning system to aim to progress an efficient elearning process becomes a critical issue. This paper proposes applying the OFMM (Opinion Features Mining Model) to determine the personal learner’s opinions from learner’s reviews.